The Dunhuang Grottoes and Global Education: Philosophical, Spiritual, Scientific, and Aesthetic Insights - Di, Xu (Spirituality, Religion, and Education, 2019)
1. Introduction -- 2. Dunhuang's Infinite Connections with Education -- 3. Dunhuang and Educational Philosophy -- 4. Lessons in Moral Education from Dunhuang Murals -- 5. The Philosophy of Aesthetic Education of Ch'an Buddhism: A New Interpretation on the Mandala Sutra of the Sixth Patriarch from Dunhuang -- 6. West Meets East - The Interplay of Unity and Diversity -- 7. Enlightenment from Body-Spirit Integration: Dunhuang's Buddhist Cultivation Pathways and Educational Applications -- 8. Dunhuang as a Model for EthnoSTEM Education -- 9. The Significance of the Dunhuang Mogao Frescos for Universal Education Today -- 10. An Examination of Dunhuang Education from Psychological Perspective: Heart, Soul, and Our Lives -- 11. Dunhuang and Contemporary Music Education -- 12. Dunhuang and Basic Education -- 13. Dunhuang Grottoes and Lifelong Learning -- 14. Harmonious Coexistence with Nature: Naturalistic Education in the Dunhuang Frescoes